Light Bulbs and Round Tables : A Conversation about MA in Curating at Aarhus University - Sandvad Mengers, Line; Balslev Strøjer, Nanna; Friis Sørensen, Trine (Peripeti, 2022)
Why seek further education when working in the curatorial field? How does practice and theory feed off each other in curatorial work? And what is the status of the white cube? Do we need to move beyond this naturalised institution of exhibition making in order to engage with the urgencies of today? These are the main questions of the conversation between Line Sandvad Mengers and Nanna Balslev Strøjer, curators and graduates of the study programme MA in Curating at Aarhus University, and programme coordinator Trine Friis Sørensen.